THE STUDY OF MINDSET AND BEHAVIOR OF BUSINESSMEN ON THE THEORY OF 7 SPIRITS OF ENTREPRENEURSHIP - utami, christina whidya; Oetomo, Jonathan A (International Business Management - Universitas Ciputra, 2019)
Being an entrepreneur maybe is a dream for most of people. Before becoming an entrepreneur, we need to know what is the mindset and the behavior of entrepreneurs who has been there before. Ciputra University is a higher education institution founded by Ir. Ciputra teaching about 7 spirit of entrepreneurs consisting of passion, independent, market sensitivity, creative and innovative, calculated risk taker, persistence and high ethical standard as a guide for entrepreneurs who wanted to start or undergoing a business. This research with title “Mindset and Behavior Studies in 7 spirit of entrepreneur theory” performed with qualitative method towards 4 interviewees that has been running business for more than 5 years and had more than 10 employees. Data will be collected by interviewing to 4 interviewees. The result of this research says, that 7 spirit of entrepreneurs theory does exist and reflected in a mindset and behavior of entrepreneurs.